2011
DOI: 10.3109/15419061.2011.606381
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Pathophysiology of Selectins, Integrins, and IgSf Cell Adhesion Molecules Focusing on Inflammation. A Paradigm Model on Infectious Endocarditis

Abstract: The development of adhesion bonds, either among cells or among cells and components of the extracellular matrix, is a crucial process. These interactions are mediated by some molecules collectively known as adhesion molecules (CAMs). CAMs are ubiquitously expressed proteins playing a central role in controlling cell migration, proliferation, survival, and apoptosis. Besides their key function in physiological maintenance of tissue integrity, CAMs play an eminent role in various pathological processes such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 94 publications
(110 reference statements)
0
39
0
3
Order By: Relevance
“…In addition to atherosclerosis, adhesion molecules such as ICAM-1 are also implicated in the progression of infection (35)(36)(37). A recent study reported that manganese blocks intracellular trafficking of Shiga toxin and that manganese-supplemented mice were completely resistant to a lethal Shiga toxin challenge (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to atherosclerosis, adhesion molecules such as ICAM-1 are also implicated in the progression of infection (35)(36)(37). A recent study reported that manganese blocks intracellular trafficking of Shiga toxin and that manganese-supplemented mice were completely resistant to a lethal Shiga toxin challenge (38).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are transmembrane receptors that are the bridges for cellcell and cell-extracellular matrix interactions with other receptors such as cadherins, the immunoglobulin superfamily cell adhesion molecules [22]. The ITGB3 protein may combine with multiple partners resulting in different integrins.…”
Section: Differential Proteome and Extracellular Matrix (Ecm) In Siasmentioning
confidence: 99%
“…This is a complex and multi-mediated process that results from the release of inflammatory mediators and involves proteins with lectin domains, the selectins [20]. These proteins, which are present both in neutrophil and endothelial cells, interact with their respective carbohydrate ligands mediating the process called rolling.…”
Section: Introductionmentioning
confidence: 99%